CHANGING PORTRAYALS OF ASIANS IN FILMS - Sudirman, Eka Pratiwi; Kuncara, Singgih Daru; Mubarok, Ahmad (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This research focuses on an anti-whitewashing movement in films and how it connects with the shifting portrayals and stereotypes of Asians in films. The period addressed in this study is from 1995 to 2021. The researcher begins by recognizing whitewashing issues and concerns in casting Asian actors and identifying stereotypical images of Asians portrayed in two films: the original version of Mortal Kombat, which was released in 1995, and the contemporary remake of the film, which was released in 2021. This research used content analysis to compare the portrayals and stereotypes of Asians in both films. The data indicate that racist images of Asians seen in Mortal Combat 1995 have been removed in Mortal Combat 2021.